(untitled) (Bulletin KNOB, 2005)
Onsenoort is a good example of a late 14th-century tower block. The tower was rebuilt in 1388 by Jan Kuyst Arent Dirkszn, Hegeman of Albrecht van Beieren, governor of the count of Holland, to replace a destroyed predecessor. Initially, unlike most towers from the 13th century, Onsenoort is not a high tower with relatively thin walls, but low (just a cellar and a ground floor) with thick walls and consequently clearly intended for the function of military bulwark. In view of its situation in the borderland between the provinces of Brabant and Holland this is not surprising. Its defensibility is further strengthened by a surrounding moat and the relatively closed construction of the cellar. The tower was not exclusively intended for defense, but was also suitable for residential purposes, as appears from a fireplace and toilet. After the tower had been heightened in the 15th century, which did not make it more defensible but rather more suitable for habitation, the tower lost its military significance in the 16th century. The function of Onsenoort changed into a more representative residence through the construction of a new house. The tower was deliberately retained and as a symbol it refers to the defensible medieval character of the castle. In 1903 the castle passed from the hands of the nobility into the hands of the clergy and was eventually converted into an abbey. Unlike virtually all later buildings the tower was retained and even heightened. These past years the tower has been renovated and fitted out for local cultural activities. Thus its very defensive medieval character was altered into an inviting and inspiring one.